(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the frequency of Group B Streptococcal Infection in Patients with Preterm Premature Rapture of Membranes Study Design: Descriptive case series study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynaecology, Fatima Memorial Hospital, Lahore from 13rd April 2018 to 13rd October 2018. Materials and Methods: Data was collected through non-Probability consecutive sampling technique. Sample size of 150 cases with any parity presenting in the third trimester were included in the study after taking informed consent. Demographic data (Name, Age, Gestational age, parity and BMI) was recorded. Vaginal swab of all high-risk obstetrical patients fulfilling inclusion criteria was taken and sent for culture and sensitivity. Results: The mean age of the patients was noted 26.2 ± 4.46 years and the mean gestational age was observed 34.34 + 1.58 weeks. Out of these 150 pregnant women who presented with preterm or PPROM; GBS positivity was found in 32 (21.3%) patients. All these patients (100%) were treated with intrapartum antibiotic prophylaxis and were followed until delivery for neonatal outcome. Early onset of GBS disease in neonates was reported in 5 (15.6%) among the patients treated with antibiotic. Conclusion: It is concluded that the positivity of group B streptococcus in Pakistani women is significantly higher, however our study findings indicated that intrapartum antibiotic prophylaxis can prevent GBS vertical transmission from colonized mothers to their infants.